2006
DOI: 10.1042/bj20060364
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of human YY1 and caspase 7 promoters by prohibitin through E2F1 and p53 binding sites

Abstract: Prohibitin is a 30 kDa growth suppressive protein that has pleiotropic functions in the cell. Although prohibitin has been demonstrated to have potent transcriptional regulatory functions, it has also been proposed to facilitate protein folding in the mitochondria and promote cell migration in association with Raf-1. Our previous studies have shown that prohibitin physically interacts with the marked-box domain of E2F family members and represses their transcriptional activity; in contrast, prohibitin could bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 49 publications
2
31
0
Order By: Relevance
“…A recent study showed that caspase-7 is a p53 responsive gene but the p53-binding site was not identified. 25 In these studies, it was suggested that the caspase-7 gene may bind to p53 through the promoter region within À1000 bp. However, no consensus binding site for p53 was found in this region in the human or mouse caspase-7 gene.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that caspase-7 is a p53 responsive gene but the p53-binding site was not identified. 25 In these studies, it was suggested that the caspase-7 gene may bind to p53 through the promoter region within À1000 bp. However, no consensus binding site for p53 was found in this region in the human or mouse caspase-7 gene.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies found co-localization between PHB, p53 and E2F1 in the nucleus of breast cancer cells, and demonstrated PHB could activate transcription mediated by p53 and enhance binding of p53 with the promoter. It is also reported that p53-PHB complex translocated from nucleus to cytoplasm after stimulation by the signal of apoptosis [21][22][23] .…”
Section: Co-localization Of Phb With Products Of Related Genes and Itmentioning
confidence: 99%
“…Prohibitin 1 (PHB) is a ubiquitously expressed, multifunctional protein implicated in cellular processes including mitochondrial function and protein folding (Nijtmans et al, 2000;Artal-Sanz et al, 2003), proliferation control and suppression of oncogenesis McClung et al, 1995;Dell'Orco et al, 1996), and transcription regulation (Wang et al, 1999Joshi et al, 2007). PHB contains an N-terminal hydrophobic membrane anchoring ␣1-helix domain and a C-terminal leucine/isoleucine-rich motif that acts as a nuclear export signal (Rastogi et al, 2006;Winter et al, 2007).…”
Section: Introductionmentioning
confidence: 99%